PENGARUH KEPERCAYAAN DIRI DAN KECEMASAN MATEMATIKA TERHADAP HASIL BELAJAR SISWA DI SMP NEGERI 2 TONDANO - Novita Ririk; Murni Sulistyaningsih; Selfie L. Kumesan (CV. ADIBA AISHA AMIRA, 2022)
This study aims to determine the effect of 1) Self-confidence on student learning outcomes. 2) Mathematics anxiety on student learning outcomes. 3) Confidence and mathematics anxiety on student learning outcomes. This study uses a survey method of the correlational form. The population in this study were students of class VIII SMP Negeri 2 Tondano. The number of samples taken was as many as 32 students using a simple random sampling technique. The results showed that 1) Self-confidence has a positive and significant influence on student learning outcomes with a correlation coefficient of 0,557 with a relationship model and the contribution of self-confidence to learning outcomes is 31%. 2) Mathematics anxiety has a negative and significant effect on student learning outcomes with a correlation coefficient of 0,519 with a relationship model and the contribution of mathematics anxiety to student learning outcomes by 26,90%. 3) Self-confidence and mathematics anxiety have a significant effect on student learning outcomes with a correlation coefficient of 0,679 with the regression equation model with the contribution of self-confidence and mathematics anxiety to student learning outcomes of 46,10 %. Based on the results of the research that has been obtained, it is concluded that self-confidence and math anxiety together influence student learning outcomes.